Patent Analysis in the Grain Storage Sector - DU Shang-qiu; CUI Peng-cheng (Liang you shipin ke-ji)
With the increasing global emphasis on food quality, safety, and reducing grain storage losses, both domestic and international research institutions are focusing on developing new grain storage technologies and theories. This article focuses on the invention and utility model patent data in the global grain storage field, and uses patent analysis technology to present the development history and current situation of this field from multiple perspectives, clarifying industry hotspots and directions. Global patent applications in this field entered a significant development phase around 2008 and have experienced rapid growth over the past decade.. Grain storage echnologies are concentrated in major grain-producing areas and specific economically developed regions. Patent applicants are mainly distributed in universities, research institutes, and companies, with grain warehouse structure and construction, grain warehouse sampling, grain environment measurement and control, and grain pest control as technical hotspots. Although China plays a leading role in global grain storage patent development, the conversion rate of related patents remains low and largely at the research stage, with limited industrialization. China should establish a technology transfer mechanism centered on enterprises, with active participation from universities and research institutes, fostering shared benefits and risks. Strengthening collaboration between industry, academia, and research is essential to promote the transformation and industrialization of patented technologies. Additionally, focusing on global patent layout will be a key direction for the future development of China’s grain storage industry.